S133 Investigating genome wide dna methylation in airway and parenchymal fibroblasts from healthy individuals and individuals with copd. (15th November 2016) - Clifford, RL; Fishbane, N; Rajasekar, P; Fisher, AJ; Kobor, MS; Knox, AJ; Hackett, TL
Abstract : Rationale: Lung fibroblasts are implicated in respiratory disease pathology including chronic obstructive pulmonary disease (COPD). Phenotypic differences between fibroblasts isolated from the airway versus the parenchyma have been described but no studies have compared the cell types on a genome wide scale. DNA methylation is a reversible modification of the DNA structure with the ability to affect cell function via the alteration of gene expression. Here we compared genome wide DNA methylation profiles from airway and parenchymal fibroblasts and assessed modification to these profiles in cells isolated from individuals with COPD. Methods: DNA was isolated from parenchymal and airway fibroblasts at passage 4, and bisulphite treated. Site specific, quantitative genome wide methylation was determined using the Illumina 450K Infinium Methylation BeadChip array. Linear modelling and DMRcate functions identified differentially methylated sites and regions respectively between airway and parenchymal fibroblasts isolated from individuals with normal lung function versus those with COPD. Results: 3980 CpG (methylation) sites significantly differed after Bonferroni correction between airway and parenchymal fibroblasts isolated from healthy individuals. These sites had a broad distribution of effect size, with 240 CpG sites displaying a difference in methylation of >50%. 78 of these sites validated in a second cohort of 7 sets of paired airway and parenchymal fibroblasts isolated from the same individual. There was genomic proximity to these sites and DMRcate was used to refine the individual CpG sites to 5 regions of interest associated with 5 genes; HLX, TWIST1, CREB5, SKAP2 and PRDM16. Differences in methylation were less pronounced when comparing cells isolated from healthy individuals to those with COPD. In airway fibroblasts 47 DMRcate regions were identified with a maximum difference in methylation of at least 20%. In parenchymal fibroblasts 3 DMRcate regions were identified with a maximum difference in methylation of at least 20%. Conclusions: DNA methylation profiles are significantly different between airway and parenchymal fibroblasts but only small modifications are associated with COPD. Future work will focus on validating a methylation based markers of parenchymal versus airway fibroblasts and associating our differential observations with gene/protein expression.